Educational strategies to reduce the gender gap in the self-efficacy of high school students in stem teaching - Brage-del-Río, María; Martin-Núñez, Jose Luis; Pablo-Lerchundi, Iciar (Frontiers in Education, 2025)
In the current educational context, the equal participation of women and men in STEM fields remains a challenge. Despite the progress, there are still significant disparities between the number of men and women who study and dedicate their professional lives to scientific careers. The main objective of this study is to determine whether there is a gender difference in self-efficacy in Physics and Chemistry among pre-university students with the same academic performance. The participants of this study are a total of 525 Secondary Education students in Madrid (Spain). By relating the results of a self-efficacy survey to the students’ academic grades and their gender, it was possible to analyze the impact of gender on the participants’ self-efficacy. ANOVA analyses results show that there is a gender gap for the entire sample and that this is particularly notable in the crucial years when students are deciding on their academic careers. These findings emphasize the importance of early intervention to enhance the self-efficacy of female students in scientific disciplines. In response to this issue, three potential methodological approaches have been suggested: fostering cooperative learning, incorporating self-assessment and metacognitive activities, and introducing female role models. These approaches should be carefully implemented to prevent unintended negative effects. This strategy will not only foster equal opportunities but also enhance the innovative capacity and socio-economic growth of our society.